Water policy and institutions in the Republic of Korea - Namsoo Lee (Asian Development Bank Institute (ADBI), 2019)
This study reviews the water policies and institutions for water management in the Republic of Korea over a 50-year period during which the country developed from a war-torn nation into one of the 10 largest economies in the world. The Republic of Korea's water policy commenced in the form of comprehensive water resources development projects starting with basin investigations in the 1960s after the Korean War. The comprehensive development projects included large-scale dams and water control projects in major rivers in the 1970s and 1980s. The concept of eco-friendly water resources management was born in the 1990s, and the focus on water supply and/or control moved to sustainable water management including stream environment preservation in the 2000s. Since 2010, the policy has focused on coping with climate change and advancing the water management system. The paper provides lessons for developing countries that otherwise prioritize investment in roads, transportation, communication, and electricity ahead of water. The experience of the Republic Korea shows that water should also be regarded as a necessity both for the citizens' daily lives and industrial activities.
Keywords: L95; Q25; O13; 330; Republic of Korea; water management; water supply systems; water pricing